Could vitamin D concentration be a marker of a long hospital stay in older adults patients? - Nowak, Justyna; Jabczyk, Marzena; Jagielski, Paweł; Hudzik, Bartosz; Brukało, Katarzyna; Borszcz, Jakub; Zubelewicz-Szkodzińska, Barbara (Frontiers in Nutrition, 2023)
Background and aims Vitamin D plays a pleiotropic role in the human body. Some studies have suggested that hypovitaminosis D may serve as a marker of comorbidity severity and length of hospital stay. Hospitalized older adults patients with a higher comorbidity burden tend to have lower vitamin D status, which negatively impacts the length of their hospital stay. Vitamin D deficiency has been identified as a significant risk factor for a prolonged hospital stay. This study aimed to investigate the link between vitamin D status and prolonged hospital stays, focusing on geriatric patients, and to assess the variation in hospitalization duration among geriatric patients with different vitamin D statuses. Methods The study sample comprised of 422 patients aged over 60 years admitted to the geriatric department. Blood samples were collected in the morning on the day of admission. According to the diagnostic threshold defining serum 25(OH)D concentration approved for Central Europe, patients were divided into two groups (deficiency group and suboptimal group). Patients were divided into two groups based on hospitalization duration: the first, “shorter hospitalization,” included stays up to 11 days, whereas the second, “longer hospitalization,” encompassed stays of 12 days and above. Results In total, 242 Caucasian patients, primarily women (172 women and 70 men), were recruited in the study. Patients with vitamin D deficiency had extended hospital stays compared with those with vitamin D levels below 49.92 nmol/L: 10.0 (8.00–13.00) days vs. 9.00 (8.00–11.00) days, P = 0.044. Hospitalization length (in days) had a negative correlation with vitamin D blood status (nmol/L) (P = 0.0005; R = −0.2243). ROC analysis indicated that patients with vitamin D levels below 31.2 nmol/L had a 47% higher chance of extended hospitalization, whereas those with levels above 31.2 nmol/L had a 77% higher chance of avoiding it. A significant majority of patients with suboptimal 25(OH)D levels experienced shorter hospital stays (≤11 days) than those with vitamin D deficiency (64.6%), P = 0.045. Conclusion The study findings indicate that lower serum levels of 25(OH)D in hospitalized patients within the geriatric department are linked to extended hospital stays. Vitamin D holds potential as a predictor of hospitalization duration in geriatric patients. Nonetheless, further research is imperative to account for additional factors affecting health status and hospitalization duration in older adults individuals.